Water level control of small-scale recirculating aquaculture system with protein skimmer using fuzzy logic controller - Mulyanto, Mulyanto; Suprapty, Bedi; Gaffar, Achmad Fanany Onnilita; Sumadi, Muhammad Taufiq (Institute of Advanced Engineering and Science, 2023)
The recirculating aquaculture system (RAS) is a land-based aquaculture facility, either open-air or indoors, that minimizes water consumption by filtering, adapting, and reusing water. Solid organic matter from fish waste and food waste directly becomes waste that needs to be eliminated because it is a source of increasing total ammonia nitrogen (TAN), total suspended solids (TSS), total dissolved solids (TDS), and also has an impact on reducing dissolved oxygen (DO). RAS requires a water level control system so the fish tank does not experience water shortages or floods, disrupting the aquatic aquaculture ecosystem. In this study, small-scale RAS is modeled using a 3-coupled tanks system approach with a tank configuration that follows the most straightforward RAS water recirculation process (fish tank, mechanic filter, biofilter). Clean water from the reservoir flows into the fish tank through a protein skimmer. This study applies the fuzzy logic controller (FLC) to control the water level in the protein skimmer and biofilter tanks by controlling the position of several valves where the placement positions of the valves have been determined according to system requirements. The study results show that the tuned single-input FLC has the best average output response characteristics with ts=50, h1ss=49.98, ess=0.02 in protein skimmer and ts=4700, h1ss=39.75, ess=0.25 in the tank system.